Update and New Insights on Future Cancer Drug Candidates From Plant-Based Alkaloids - Tilaoui, Mounir; Ait Mouse, Hassan; Zyad, Abdelmajid (Frontiers in Pharmacology, 2021)
Cancer is a complex multifactorial disease that results from alterations in many physiological and biochemical functions. Over the last few decades, it has become clear that cancer cells can acquire multidrug resistance to conventional anticancer drugs, resulting in tumor relapse. Thus, there is a continuing need to discover new and effective anticancer drugs. Natural products from plants have served as a primary source of cancer drugs and continue to provide new plant-derived anticancer drugs. The present review describes plant-based alkaloids, which have been reported as active or potentially active in cancer treatment within the past four years (2017–2020), both in preclinical research and/or in clinical trials. In addition, recent insights into the possible molecular mechanism of action of alkaloids prodrugs naturally present in plants are also highlighted.